Relationship Among Plasma Tiglycerides, Body Mass, Reproduction of Northern Bobwhites - J. M. Mueller; C. B. Dabbert (National Quail Symposium Proceedings, 2017)
The earliest potential initiation of northern bobwhite (Colinus virginianus) reproduction is limited by photoperiod. Secondary factors such as lipid reserves, diet, and stress often limit the beginning of northern bobwhite reproduction, potentially reducing reproductive success and causing a shorter reproductive season. We measured late winter body masses and plasma triglycerides of wild northern bobwhites and subsequent reproductive timing and effort in 1997 and 1998 on the coastal prairie of Texas. Using body mass and plasma triglyceride levels as indices of body fat, we tested the hypothesis that the onset of reproduction and first clutch size was influenced by late winter lipid reserves. Northern bobwhite plasma triglycerides were higher (P < 0.001) and more variable (P = 0.019) in 1998, and nesting began 15 ± 1.6 days (c ± SE) earlier than in 1997. However, within each year, no combination of body mass and triglycerides was associated with timing of nesting or size of first clutch (P > 0.1). In addition, body masses were not correlated with plasma triglycerides (P > 0.1). Our findings suggest that individual plasma triglyceride levels and body mass are unsuitable variables for assessing within-population differences in reproductive timing. However, mean plasma triglycerides for a population may be useful for assessing differences in reproductive timing among years and locations. The relationship between triglycerides and hormones directly affecting gonadal recrudescence, such as luteinizing hormone (LH) and prolactin, is uncertain for wild northern bobwhites. Thus, future studies should assess causes and patterns of change in these hormones.
Keywords: body mass; Colinus virginianus; northern bobwhite; reproduction; triglycerides